ANALISIS INPUT OUTPUT PROVINSI KALIMANTAN TIMUR TAHUN 2016 : IDENTIFIKASI SEKTOR UNGGULAN - Yosi Octaviani Simanjutak; Aditya Wisnu Anggara (BPS Kalimantan Timur, 2022)
The economy of Kalimantan Timur Province is still dominated by the Mining and Quarrying Sector, besides natural resources of that sector are non-renewable, the sector's contribution has also decline over the last three years. Therefore, a study of Input-Output (IO) analysis was carried out on the linkages of economic sectors in Kalimantan Timur Province to identify other sectors with potential and analyse the multiplier effect of output, labour, and income. This study uses the IO Table of Kalimantan Timur Province in 2016 and employment data in 2016. The results of the analysis of inter-sector linkages and output multipliers show that the Electricity and Gas Procurement, Water Supply, Waste Management, Waste and Recycling sectors are sectors that can increase the economic output of Kalimantan Timur Province. The Community, Social and Individual Services Sector is the highest employment multiplier capable of increasing employment opportunities in this sector. The Agriculture, Forestry and Fisheries sectors are the highest income multipliers to increase the income of all economic sectors in the Kalimantan Timur Province.